1996
DOI: 10.1152/ajprenal.1996.270.5.f886
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous origin of glomerular endothelial and mesangial cells in grafts of embryonic kidneys

Abstract: To address origins of glomerular endothelial and mesangial cells in embryonic mammalian kidneys, we established interspecies grafts between rats and mice, in which fetal kidneys were implanted into the anterior eye chamber of adult hosts. After 5-7 days, hosts bearing grafts received intravenous injections with species-specific monoclonal antibodies (MAbs) to matrix components. In all cases, glomerular basement membranes and mesangial matrices labeled solely for donor-derived matrix. Additionally, microvessel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
98
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 0 publications
13
98
1
Order By: Relevance
“…As expected, the GFP + MM cells within the cultured chimeric explants had the capacity to incorporate to the epithelial tubules ( Figure 4 40,41 and FACS. In the organ culture condition, the Foxd1 + cells also remain distinct from the Pax2 + ones representing the nephron precursors ( Figure 5, A-D).…”
Section: Generation Of Chimeric Kidney Mesenchymal Aggregates Indicatsupporting
confidence: 75%
“…As expected, the GFP + MM cells within the cultured chimeric explants had the capacity to incorporate to the epithelial tubules ( Figure 4 40,41 and FACS. In the organ culture condition, the Foxd1 + cells also remain distinct from the Pax2 + ones representing the nephron precursors ( Figure 5, A-D).…”
Section: Generation Of Chimeric Kidney Mesenchymal Aggregates Indicatsupporting
confidence: 75%
“…[23][24][25] Whereas our studies suggest that SCL+ precursors originate locally in the kidney, the fact that we found cells derived from the SCL+ precursors labeled at E6.5 or E9.5, before the kidney starts to form, indicates the possibility that precursors from the yolk sac and AGM may have seeded the intermediate mesoderm before the condensation and development of the "avascular" metanephric mesenchyme.…”
Section: Discussionmentioning
confidence: 94%
“…Interspecies cross transplantation experiments of prevascular embryonic kidneys were originally performed into quail chorioallantoic membrane because of the presence of a characteristic quail nuclear marker that could easily track the contribution of the host tissue. 25,35 Those experiments show the presence of hostderived ECs and mesangial cells within the embryonic kidney and suggest an extrarenal source for ECs and mesangial cells. The development of genetically-labeled mice with traceable reporters allowed further experiments in mice.…”
Section: Progenitors Of Mural Cells Pericytes and Interstitial Cellsmentioning
confidence: 89%
“…It is also clear that those precursors differentiate into all of the cell types necessary for the development of the kidney arterioles, including endothelial cells (ECs), smooth muscle cells (SMCs), and renin cells. 24,25 Furthermore, crosstransplantation studies of those embryonic prevascular kidneys under the kidney capsule of a host mouse allowed us and others to demonstrate that precursor cells have the capacity to differentiate, acquire the right positional information, and fully assemble to form the kidney arterioles. 24 The origin, lineage relationships, and morphogenesis of the kidney vasculature are also not well understood.…”
Section: Vascular Progenitors and Arteriolar Developmentmentioning
confidence: 99%